1994
DOI: 10.1111/j.1365-2710.1994.tb00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of amoxycillin and potassium clavulanate in co-amoxiclav oral suspension

Abstract: A study was carried out using high performance liquid chromatography (HPLC) to determine the chemical stability of amoxycillin and potassium clavulanate in 250/62 co-amoxyclav oral suspension (Augmentin), stored at room temperature (RT, 20 degrees C) and 8 degrees C over a period of 11 days. The suspension was judged to be acceptable if its components maintained at least 90% of their label concentrations. During the test period, the amoxycillin component was found to be more stable than the clavulanate. Amoxyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Similarly, the concentration of Arthemether differs slightly from the manufacturer claim (80 mg), this variation could be attributed to the storage temperature and the difference is above the recommended standard. The results of these analysis is similar to the study carried out by Mehta et al [21] which shows that amoxicillin and potassium clavulanate (250/62 Co-amoxiclav) oral suspension stored at room temperature 20°C and 8°C over a period of 11 days showed that amoxicillin is stable for 7 days at both temperatures. Also in agreement is the work by Naidoo [22] which showed that amoxicillin suspension stored between 2°C and 8°C for 7 days showed the lowest level of degradation.…”
Section: Resultssupporting
confidence: 79%
“…Similarly, the concentration of Arthemether differs slightly from the manufacturer claim (80 mg), this variation could be attributed to the storage temperature and the difference is above the recommended standard. The results of these analysis is similar to the study carried out by Mehta et al [21] which shows that amoxicillin and potassium clavulanate (250/62 Co-amoxiclav) oral suspension stored at room temperature 20°C and 8°C over a period of 11 days showed that amoxicillin is stable for 7 days at both temperatures. Also in agreement is the work by Naidoo [22] which showed that amoxicillin suspension stored between 2°C and 8°C for 7 days showed the lowest level of degradation.…”
Section: Resultssupporting
confidence: 79%
“…Mehta et al observed 90% conservation of reconstituted oral amoxicillin at 20°C for only 7 days [19], while Peace et al report only 79% conservation at 7 days at a temperature of 27-29°C [20]. Currently there are few data on the stability of oral amoxicillin tablets.…”
Section: Amoxicillinmentioning
confidence: 99%
“…Its stability in aqueous solutions has been poorly characterized, though one recent study noted that in sodium chloride, stability was maintained for 8 hours at 4°C and for only 4 hours at 20°C. Reconstituted oral suspensions appear to be somewhat more stable; at 8°C, clavulanic acid maintains at least 90% of its initial concentration for 7 days, though at 20°C only 60% is maintained in the same time period [19], and at 27-29°C, only 55% [20].…”
Section: Clavulanic Acidmentioning
confidence: 99%
“…However, the lack of clean water and electricity in developing areas makes this fight highly challenging for humanitarian agencies and local/mobile healthcare workers. , For example, amoxicillin is an inexpensive and highly effective drug used against a number of pathogens, including Streptococcus pneumoniae, the most common cause of community-acquired pneumonia. , It is one of the most commonly prescribed antibiotics for children, being on the list of essential medicines recommended by World Health Organization . Amoxicillin is commercially produced as a powder and readily available in the market in a variety of drug formulations including syrups, reconstituted aqueous suspensions, capsules, chewables, and tablets. , Liquid-based formulations of amoxicillin require stringent storage conditions (i.e., refrigeration) to prevent activity loss due to degradation. The use of nonliquid-based forms (i.e., capsules, chewables, and tablets) constitute a viable option to prevent amoxicillin degradation due to hydrolysis. , However, such options are not quite convenient for infant/toddler patients who cannot safely swallow or chew hard substances. , Thus, there is a great need for an infant/toddler-friendly formulation for patients in the low-income countries, with limited clean water and electricity.…”
Section: Introductionmentioning
confidence: 98%